2018
DOI: 10.3329/seajph.v7i2.38853
|View full text |Cite
|
Sign up to set email alerts
|

School-based educational intervention to improve children’s oral health-related behaviors in rural Bangladesh

Abstract: Children in rural Bangladesh have limited access to oral health services. As a pilot project, a one-day one-time oral health educational intervention was conducted at a primary school in Tangail district in Bangladesh. This study assessed the effect of this educational intervention on the children’s oral behaviors using controlled pre- and post-intervention design. Fifty-two students at the intervention school and 37 students at a control school agreed to participate in this study. A baseline survey was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Bhuiyan et al reported that primary school children have limited awareness about oral health and poor knowledge of oral hygiene habits and it creates muchneeded niche for implementing school-based oral health awareness and education programs [29]. This is also supported by other studies in Bangladesh [30][31][32]. There was also prevalence of CSOM, external angular dermoid, and inguinal hernia.…”
Section: Discussionmentioning
confidence: 85%
“…Bhuiyan et al reported that primary school children have limited awareness about oral health and poor knowledge of oral hygiene habits and it creates muchneeded niche for implementing school-based oral health awareness and education programs [29]. This is also supported by other studies in Bangladesh [30][31][32]. There was also prevalence of CSOM, external angular dermoid, and inguinal hernia.…”
Section: Discussionmentioning
confidence: 85%
“…Poor health behavioral practices, including insufficient awareness and knowledge, increase the risk of malnutrition and infectious diseases (Sujan et al, 2020). Moreover, proper sanitation and hygiene facilities in the school setting also need to be considered (Jordanova et al, 2015), and it is an ardent necessity to place school nurses and health education at the primary school level, especially in LMICs (Yang et al, 2018) to improve children's health status, hygiene behavior, awareness, and knowledge (Furukawa et al, 2018; Kurscheid et al, 2018).…”
Section: Discussionmentioning
confidence: 99%